Teaching Speaking Through Short Dialogue At The Eleventh Grade Students of SMAN 1 Pelaihari - Erni Nadia (STKIP PGRI Banjarmasin, 2019)
Speaking is the process of building and sharing meaning through the use of verbal and non-verbal symbols. Speaking is a crucial part of second language teaching and learning. The objective of this research is to describe how the process of teaching speaking through short dialogue at the Eleventh grade students of SMAN 1 Pelaihari school year 2019/2020. This research paper is aimed at describing the process of teaching speaking through short dialogue focused on the curriculum, method and technique of teaching speaking, teaching media, and system of evaluation. The source of data is teaching learning process of dialogue technique at SMAN 1 Pelaihari and documents. In this research, the writer does the classroom observation, interview and document to the English teacher. Based on the data analysis, the writer finds that the result of teaching speaking by using short dialogue at the eleventh grade students of SMAN 1 Pelaihari as follows: 1). The curriculum of SMAN 1 Pelaihari, especially at the eleventh level, uses Kurikulum 2013. In Kurikulum 2013, the goal of teaching speaking is to gain the students to be able to communicate in English on the elementary level. Consequently, they can express various feelings or senses; 2). Method and technique of teaching speaking. In teaching speaking the English teacher uses Communicative approach and dialogue technique; 3). Media of teaching speaking. Media a very needed to successful teaching learning process, so the English teacher of SMAN 1 Pelaihari uses a whiteboard and cassette (CD); and 4). System evaluation of speaking activities. To evaluate the students' performance the teacher gives comments and mark, this way is very needed for a teacher to know the student's capability and to make the lesson better. Therefore, the result of teaching speaking through dialogue is satisfying.